Why did VALIDATE-SWEDEHEART not validate the results of HORIZONS? - Zeymer, Uwe (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2017)
Intravenous anticoagulation is recommended during percutaneous coronary intervention (PCI) in all patients with acute coronary syndromes to avoid ischemic and embolic complications during the procedure and improve outcome (1).